The effects of public R&D subsidized loans on firms’ R&D outputs: evidence from China - Gao, Yuchen; Zhang, Si; Hu, Yimei (Journal of Business Economics and Management, 2021)
R&D subsidized loans (tiexi daikuan) is an effective market-driven solution to promote firms’ R&D outputs, including patent applications and new product sales, in China. However, empirical examination on the effects of subsidized loans is insufficient. Using a panel data of manufacturing firms of Jiangsu Province from 2010 to 2014, the study investigates the effects of R&D subsidized loans on firms’ R&D outputs in comparison to that of the direct R&D grants. The results show that R&D subsidized loan recipients significantly outperform those who only receive direct grants in terms of new product sales. Meanwhile, subsidized loans inhibit the recipients’ exploratory patent applications and discourage R&D activities with higher risks. This study contributes to R&D subsidy literature and extends the knowledge in the roles of different types of public sponsorships on firms’ innovation.